2019
DOI: 10.3390/su11174674
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Feedback Analysis of Influencing Factors and Challenges of Dockless Bike-Sharing Sustainability in China

Abstract: Dockless bike-sharing programs (DBSPs) are typical representatives of the new era of the internet economy. These schemes alleviate urban traffic congestion, reduce carbon emissions, and change people’s preferred travel modes, but they also suffer from a series of problems related to unsustainability. The sustainability performance of a DBSP is closely related to its influencing factors, which can be used to understand the main challenges of the program and consider what useful measures should be taken to overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The scientific literature provides elaborations of macro-environmental factors influencing transport systems with PESTEL method by Belwal [72], PEST method [73], STEEPLE method [74], and with SWOT analysis [75]. The research of SWOT analysis of bicycle systems can be found in the works of Ma et al [76], Mátrai and Tóth [77], Guyandi et al [78], and Yang et al [79], who investigated the connected factors that are essential to the sustainability of FFBS programs. The gap of knowledge identified is that there is a lack of scientific research that analyses macro-environmental groups of factors and their mutual influence in the BSS.…”
Section: Trip Records Of the Bssmentioning
confidence: 99%
“…The scientific literature provides elaborations of macro-environmental factors influencing transport systems with PESTEL method by Belwal [72], PEST method [73], STEEPLE method [74], and with SWOT analysis [75]. The research of SWOT analysis of bicycle systems can be found in the works of Ma et al [76], Mátrai and Tóth [77], Guyandi et al [78], and Yang et al [79], who investigated the connected factors that are essential to the sustainability of FFBS programs. The gap of knowledge identified is that there is a lack of scientific research that analyses macro-environmental groups of factors and their mutual influence in the BSS.…”
Section: Trip Records Of the Bssmentioning
confidence: 99%
“…The research about bike-share is abundant and growing rapidly. Previous studies may be summarized into the following topics: history, growth and challenges of bike-sharing ( 29 ), determinants ( 3032 ), users’ travel patterns ( 3335 ), demand forecasting ( 3638 ), bicycle redistribution issues ( 39 , 40 ), and infrastructure enhancements ( 41 , 42 ). Fishman suggested “improved public transport integration” as one of the most important future directions in the bike-share literature ( 43 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang and Zhou [33] adopted a difference-indifference model to achieve similar results by using panel data from 96 cities in the United States. However, with the rapid development of shared bicycles in China, a series of unsustainable issues have been exposed in Chinese cities, including oversupply of BS, discretionary parking and illegal cycling; and inadequate regulations and market supervision [34]. Mitra et al [35] also found that the presence of public bicycles has not changed the mode of transportation for most people, and it is very unlikely that young people will switch from automobiles to bicycle riding.…”
Section: Literature Reviewmentioning
confidence: 99%